Implementation of Character Education on Student Behaviour at Gandasoli Elementary School - Mutiara, Dewi; Sofiawati, Esmi Tsalsa; Hudayani, Ria Dewi (JEdu: Journal of English Education, 2025)
In elementary school, the implementation of education for children is very weak, so it cannot guarantee character education learning. This study aimed to determine the impact of character education on student behavior at Gandasoli State Elementary School. This research uses a qualitative method, which is descriptive research. Data collection techniques were conducted by interview, observation, and documentation. Character education in elementary schools can be implemented through the learning process, school regulations, and extracurricular activities. The implementation applied at Gandasoli State Elementary School has six characteristics, namely: Implementation of tolerance character education, implementation of honest character education, implementation of hard work character education, implementation of creative character education, and implementation of discipline character education. The results of the research conducted on the behaviour of students at Gandasoli State Elementary School in the implementation of character education is follows. This can be seen from the results of observations that the behaviour of students who are taught religious values, honesty, tolerance, and discipline values are higher when students are at school.